Management of non-small cell lung cancer harboring epidermal growth factor receptor mutations in the era of first-line osimertinib - Hakozaki, Taiki; Okuma, Yusuke (Journal of Thoracic Disease, 2019)
Osimertinib (AZD9291, Tagrisso™), a third-generation irreversible epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI), has brought about rapid transformative changes to the treatment of EGFR-mutation-positive advanced non-small cell lung cancer (NSCLC). After acquiring resistance to first- or second-generation EGFR-TKIs, osimertinib showed greater efficacy than the combination of pemetrexed and platinum-based chemotherapy in patients with the exon 20 T790M resistance mutation in the AURA3 trial (1).